Solar-Powered Smart Shelter with QR Code Access Control - MOHAMAD FARID HAKIMI UZALI; AZUWIEN AIDA BOHARI (Progress in Engineering Application and Technology, 2026)
The increasing demand for sustainable public infrastructure has highlighted the importance of efficient energy generation and management, particularly for outdoor public shelters. In Malaysia, these shelters often provide basic electrical features such as lighting, ventilation, and charging ports. However, most lack advanced monitoring and energy management systems. This project aimed to design, implement, and test a solar-powered smart shelter equipped with Internet of Things (IoT) technology and user controls via QR codes, with the goal of improving energy efficiency and operational reliability. The system relied on a standalone photovoltaic setup, comprising a 50 W monocrystalline solar panel, a PWM (pulse width modulation) charge controller, and a 12 V battery to power direct current loads like lighting, ventilation fans, and USB charging ports. Two microcontrollers were integrated to enable real-time load management, energy monitoring, and user interaction through an IoT platform. Experiments carried out over three days in real environmental conditions showed that the system operated stably. During midday, the peak solar current ranged from 2.1 A to 2.7 A, while the battery voltage stayed between 12.15 V and 13.58 V throughout the testing period. The highest load recorded was 9.57 W, which remained well within the system’s capacity, indicating a reliable energy balance and uninterrupted operation. Future improvements may include incorporating an MPPT (Maximum Power Point Tracking) charge controller, enhancing data logging for long-term performance analysis, and conducting extended field tests under various weather conditions to further ensure system reliability. Overall, the results confirm that this smart shelter system is a practical and effective solution for sustainable, off-grid public facilities.